Draft Genome Sequence of “ Candidatus Phytoplasma oryzae” Strain Mbita1, the Causative Agent of Napier Grass Stunt Disease in Kenya - Fischer, Anne; Santana-Cruz, Ivette; Wambua, Lillian; Olds, Cassandra; Midega, Charles; Dickinson, Matthew; Kawicha, Praphat; Khan, Zeyaur; Masiga, Daniel; Jores, Joerg; Schneider, Bernd (American Society for Microbiology, 2016)
Phytoplasmas are bacterial plant pathogens with devastating impact on agricultural production worldwide. In eastern Africa, Napier grass stunt disease causes serious economic losses in the smallholder dairy industry. This draft genome sequence of “ Candidatus Phytoplasma oryzae” strain Mbita1 provides insight into its genomic organization and the molecular basis of pathogenicity.